Rotavirus Infection and Disease in a Multisite Birth Cohort: Results From the MAL-ED Study. (3rd May 2017) - Mohan, Venkata Raghava; Karthikeyan, Ramanujam; Babji, Sudhir; McGrath, Monica; Shrestha, Sanjaya; Shrestha, Jasmin; Mdumah, Estomih; Amour, Caroline; Samie, Amidou; Nyathi, Emanuel; Haque, Rashidul; Qureshi, Shahida; et al.
Summary: Significant heterogeneity in rotavirus infection and disease exists across 8 birth cohorts. Overcrowding and high stool pathogen detection were associated with higher incidence of infection and disease. Studies among older children in diverse settings are needed to understand vaccine performance. Abstract: Background: In a multicountry birth cohort study, we describe rotavirus infection in the first 2 years of life in sites with and without rotavirus vaccination programs. Methods: Children were recruited by 17 days of age and followed to 24 months with collection of monthly surveillance and diarrheal stools. Data on sociodemographics, feeding, and illness were collected at defined intervals. Stools were tested for rotavirus and sera for antirotavirus immunoglobulins by enzyme immunoassays. Results: A total of 1737 children contributed 22646 surveillance and 7440 diarrheal specimens. Overall, rotavirus was detected in 5.5% (408/7440) of diarrheal stools, and 344 (19.8%) children ever had rotavirus gastroenteritis. Household overcrowding and a high pathogen load were consistent risk factors for infection and disease. Three prior infections conferred 74% ( P < .001) protection against subsequent infection in sites not using vaccine. In Peru, incidence of rotavirus disease was relatively higher during the second year of life despite high vaccination coverage. Conclusions: Rotavirus infection and disease were common, but with significant heterogeneity by site. Protection by vaccination may not be sustained in the second year of life in settings with high burdens of transmission and poor response to oral vaccines.